(untitled) (CIPEEX, 2022)
ORANGE JUICE IS THE JUICE MOST CONSUMED IN BRAZIL IN ITS NATURAL FORM, ACCORDING TO NORMATIVE INSTRUCTION NO. 01, DATED JANUARY 7, 2000 (BRASIL, 2000), WHICH APPROVES THE TECHNICAL REGULATION ON IDENTITY AND QUALITY FOR FRUIT PULP AND JUICE THE DEFINITION OF ORANGE JUICE CONSISTS OF AN UNDILUTED UNFERMENTED DRINK OBTAINED FROM THE EDIBLE PART OF THE ORANGE (CITRUS SINENSIS) BY APPROPRIATE TECHNOLOGICAL PROCESSES. AS WITH ANY FOOD, THIS JUICE REQUIRES PHYSICOCHEMICAL ANALYSIS TO IDENTIFY SOME PROBLEMS SUCH AS PHYSICOCHEMICAL AND SENSORIAL ALTERATIONS TO INVESTIGATE AND QUANTIFY FOOD ADDITIVES AND TO CHECK FOR FRAUD AND TAMPERING IN THE PRODUCT, SINCE THESE FACTORS WHEN CHANGED INFLUENCE DIRECTLY ON THEIR QUALITY (FLORIANO, 2012). THE OBJECTIVE OF THE STUDY WAS TO PERFORM PHYSICAL-CHEMICAL ANALYZES OF NATURAL JUICES, ORANGE FLAVOR, SOLD IN PET BOTTLES, TO EVALUATE THE QUALITY AND THE SUITABILITY OF THE PRODUCTS TO ITS TECHNICAL REGULATION OF IDENTITY AND QUALITY. SIX NATURAL ORANGE JUICES WERE ANALYZED IN THE CHEMISTRY LABORATORY LOCATED IN BLOCK C OF THE UNIVERSITY CENTER OF ANÁPOLIS-UNIEVANGLICA, ALL OF WHICH WERE MARKETED IN PET BOTTLES, SEALED, WITHIN THE VALIDITY PERIOD AND KEPT UNDER REFRIGERATION, AS REQUIRED BY THE MANUFACTURER. THE TOTAL ACIDITY ANALYSIS WAS PERFORMED, WITH A TOTAL OF 7,0G/100G DETERMINATION OF TOTAL SUGARS BY THE LANE EYNON METHOD, WHERE THE REQUIRED VALUE IS AT MOST 13.00G/100G, DETERMINATION OF DRY RESIDUES BY THE METHOD GRAVIMETRIC, WHERE THE LEGISLATION DOES NOT ESTABLISH STANDARDS FOR SUCH ANALYSIS, DETERMINATION OF VITAMIN C BY THE TILLMANS METHOD, WITH A STANDARD OF 25G/100G, COLOR AND SMELL THAT SHOULD BE SPECIFIC. THE METHODOLOGIES ARE DESCRIBED BY THE INSTITUTO ADOLFO LUTZ (IAL, 2008). AND ALL THE CITED STANDARDS WERE BASED IN ACCORDANCE WITH NORMATIVE INSTRUCTION Nº 01/2000.THE RESULTS OBTAINED IN THE ANALYZES OF THE ANALYZED PRODUCTS WERE: IN VITAMIN C, THE VALUES €‹€‹FOUND IN THE SAMPLES RANGED FROM 12.5MG/100MG TO 258MG/100MG, WITH A MEAN OF 98.4MG/100MG, IN TOTAL ACIDITY DETERMINATION RANGED FROM 7, VALUES €‹€‹RANGING FROM 0.04G/100G TO 0.07G/100G, WITH AN AVERAGE OF 0.05G/100G, WERE USED IN THE DETERMINATION OF TOTAL SUGARS. THE AMOUNT OF TOTAL SUGARS WAS BASED ONLY ON GLUCOSE REDUCING SUGARS, SINCE THE ANALYSIS OF DETERMINATION OF NON-REDUCING SUGARS IN SUCROSE WAS ABSENT, BECAUSE THE JUICE IS NATURAL AND THERE IS NO ADDED SUGAR. IN THE COLOR AND AROMA ANALYZES, CHARACTERISTIC PARAMETERS WERE OBTAINED, AS DESCRIBED IN THEIR SPECIFICATIONS. IN DRY RESIDUE DETERMINATION, THE RESULTS PRESENTED WERE FROM 5.02% TO 9.02%, WITH A MEAN OF 7.23%. SUCH A STANDARD IS NOT ESTABLISHED BY LAW, SO IT WAS COMPARED WITH THE STUDY BY ANDRADE ET AL. (2014), WHO FOUND VALUES €‹€‹BETWEEN 9.22% AND 18.48%.IT IS CONCLUDED THAT OF SIX SAMPLES ANALYZED, FIVE ARE IN AGREEMENT WITH THE STANDARDS OF IDENTITY AND QUALITY OF THE CURRENT LEGISLATION, SINCE ONE OF THE SAMPLES WAS IN DISAGREEMENT FOR THE DETERMINATION OF VITAMIN C. THE STANDARDS OF IDENTITY AND QUALITY ARE OF PARAMOUNT IMPORTANCE AND REQUIRE BE FOLLOWED, BECAUSE THEY ESTABLISH THE PERMITTED VALUES €‹€‹AND THEREBY ENSURE THE QUALITY OF THE PRODUCT AND THE CONSUMER.